The Baroque and its Social Ills: Hate, Violence and Psycopathy in Tales of Disillusion (1647) by Maria de Zayas - Ann Rice, Robin (2015)
Important researchers in Intellectual History and Everyday Life have meticulously reviewed archive documents and other sources so as to conclude that the Spanish Baroque was an age of crisis and dramatic social change. All of this culminated in a general ambient of violence and anti-social behavior that lead to crimes, belief in the supernatural, addiction to gambling, and an obsession with honor, aristocratic titles, money, female chastity and excessive passions. My thesis is that Maria de Zayas reflected these social sorrows en her collection of framed novellas Tales of Disillusion from 1647. By means of a study that alternates between revisions of Baroque historical-sociological studies and a careful examination of the collection’s novellas, I prove that De Zayas has set in writing the most identified social problems of the epoch.